Effect of gamma irradiation on the uptake, translocation, and phytotoxicity of lead and cadmium in a soil–barley (Hordeum vulgare L.) system - Wang, Xiaojie; Hao, Baozhen; Ma, Jingli; Wang, Junfu (Frontiers in Plant Science, 2025)
AimsThis study investigated how gamma irradiation affects the plant growth and the migration of cadmium (Cd) and lead (Pb) within the soil-barley system.ResultsOur results demonstrated that gamma irradiation increased root length and root-shoot ratio compared with 0 Gy, as well as increased spike length, spikelet number, and spikelet grain weight. Furthermore, 50–150 Gy gamma radiation decreased Cd and Pb contents in grains compared to 0 Gy, Moreover, gamma radiation increased root bioconcentration factor for Cd and Pb (R-BCFCd and R-BCFPb, except for 120 Gy in Cd), while the BCFCd of the barley stem, leaf, and grain all decreased (except for 35 Gy in the leaf), Meanwhile, all gamma radiation treatments decreased translocation factor values from root to stem-leaf for Cd and Pb (R-S+L-TFCd and R-S+L-TFPb) at maturity, with a differential response observed in translocation factor values from stem-leaf to grain for Cd (S+L-G-TFCd). In addition, Pearson correlation analysis showed that the variability of Cd content in the grain was significantly and positively correlated with stem BCFCd (S-BCFCd), grain BCFCd (G-BCFCd), and R-S+L-TFCd. Pb content in the grain was significantly and positively correlated with grain BCFPb (G-BCFPb) and stem-leaf to grain for Pb (S+L-G-TFPb).ConclusionOur results suggest 50–150 Gy irradiation reduces heavy metal content in grains, likely by modulating physiological responses and the plant’s heavy metal transport pathways. This study offers a novel approach to low-cost pre-sowing seed treatment for mitigating grain metal contamination.